Establishing a dementia care competency framework for care partners, health and social care providers: A modified Delphi study protocol - Kelly Kay; Kateryna Metersky; Rebecca H. Correia; Arlene Astell; Colleen McGrath; Winnie Sun; Halyna Yurkiv; Victoria Smye (PLoS ONE, 2025)
Dementia care requires a wide range of knowledge and skills delivered by both unpaid care partners and health and social care providers. In Ontario, Canada, no systematic framework currently aligns educational content with dementia care competencies. This gap risks the effectiveness of dementia-related education and care delivery. Therefore, this study protocol describes our approach to achieve consensus on the behavioural statements that describe the core competencies required of care partners, health and social care providers involved in dementia care. We will use a two-round modified Delphi method with expert panellists from two groups: (1) care partners with experience caring for someone living with dementia and (2) interprofessional health and social care providers working with people living with dementia. We will purposively recruit up to 80 panellists (40 per group). Panellists will assess standardized behavioural competency statements derived from earlier study phases, rating them on importance and measurability using a nine-point Likert scale. Round 1 will include opportunities for panellists to suggest new statements. Statements reaching ≥70% agreement (rated 7–9 on a 9-point Likert scale) and demonstrating a narrow interquartile range (IQR ≤ 2) will advance to Round 2. In the second round, a higher consensus threshold (≥80%) and stability in ratings (median shift ≤1 point) will determine final inclusion. Qualitative feedback through open-ended questions will be analyzed alongside quantitative results to refine the statements. Findings will support the development of a consensus-based Dementia Care Competency Framework to guide evidence-based educational initiatives and care delivery across settings. This inclusive approach will provide a model for ensuring both lived experience and clinical expertise shape the future of dementia care education in Canada and beyond.